Pengembangan Modul Pembelajaran Tematik Terpadu Berbasis Model Inkuiri Untuk Siswa Kelas V Sekolah Dasar - Marcelina, Shella; Amelia, Monica (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This study has several problems, namely te learning taught by educators is lesseffective, based on observatins there are teaching aterials in the form module teaching matrials used by student are: a) there is no problem submision, b) there is no visible hypohesis formulation, c) the color of the image used is less attractive. Based on this, a learning module with themes 2 clean air for health was developed, sub-theme 1 how the body manages clean air learning 1 and 2. This study aims to produce modules that are valid, practical, and efective. This type of research is research an evelopment (R&D) using a 4-D model (define, design, develpment, diseminate). This research was conducted i a lmited manner due to the covid-19 pandemic. Based on the result of the validation of the level of validity feasibility (3.50%), material (3.27%),and language (3.37%). The result of the practicalty test for students get an average value (90%). For learning 1 and (89.9%) for learning 2 proving that the develpment of an integated thematic learning module based on the Inquiry model is valid, practivcal, effective, and feasible to use